2017
DOI: 10.1016/j.solener.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Solar assisted heat pump system for multifamily buildings: Towards a seasonal performance factor of 5? Numerical sensitivity analysis based on a monitored case study

Abstract: The present work analyses the potential of a combined solar thermal and heat pump (HP) system on new and existing multifamily buildings. The study uses numerical simulation as a complement to a monitored case study. After a description of the case study and a summary of the monitoring results, we present the numerical model developed for this study. Simulation results are validated with the monitored values, at component and system level, in terms of monthly profiles and yearly integrals. On this basis, we car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…Del Amo et al [21] reported measurements from an energy system in a building in Zaragoza with PVT collector and validated a simulation model with the measured data. Fraga et al [22] did a study on SAHP in a multifamily building, developed a numerical model of the system and conducted a sensitivity analysis for sizing the system. Dupeyrat et al [23] characterized a prototype PVT collector and simulated the performance of a solar hot water system and concluded that the combined PVT panel had advantages over separated PV and solar thermal collectors.…”
Section: Solar Assisted Heat Pump Systems -Experimental Studiesmentioning
confidence: 99%
“…Del Amo et al [21] reported measurements from an energy system in a building in Zaragoza with PVT collector and validated a simulation model with the measured data. Fraga et al [22] did a study on SAHP in a multifamily building, developed a numerical model of the system and conducted a sensitivity analysis for sizing the system. Dupeyrat et al [23] characterized a prototype PVT collector and simulated the performance of a solar hot water system and concluded that the combined PVT panel had advantages over separated PV and solar thermal collectors.…”
Section: Solar Assisted Heat Pump Systems -Experimental Studiesmentioning
confidence: 99%
“…Within this context, a recent study concerns a long term in-situ monitoring of a combined parallel/series air + solar HP system implemented on a MFB with very low heat demand situated in Geneva (Fraga et al, 2015), which resulted in a SPFsys of 2.9. In addition, a numerical study allowed to quantify the optimization potential of the specific system, to investigate the sensitivity to SH and DHW demands, in particular concerning the applicability of the concept in the case of building retrofit, as well as to define design guidelines for such systems (Fraga et al, 2017).…”
Section: Objectivesmentioning
confidence: 99%
“…This study also tested different preheating times, taking into account the outdoor temperature and achieving cost savings of 16-19 %. The work presented in [18] also analyses the potential of a heat pump system, but in this case coupled with solar thermal energy on multifamily buildings. They concluded that the related investment may not be worthwhile, given the rather small associated electricity savings.…”
Section: Reported Cost Savingsmentioning
confidence: 99%